Early Childhood Education in Surah Maryam: Perspective of Tafsir Al-Qurthubi: English - Sofiani, Indah; Mahfud, Mahfud; Anshorullah, Arich H. (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2024)
In discussions about education, early childhood education has become a primary focus. The question is, when is the ideal time to begin this education? While many believe that education starts after a child enters school or preschool, research indicates that education actually begins during pregnancy. Al-Qur’an, as the guiding principle for Muslims, emphasizes the importance of early education. Therefore, studying Al-Qur’an is an obligation for every Muslim. This study focuses on early childhood education based on the Surah Maryam (Chapter of Mary) in the commentary by Imam Al-Qurthubi. The research method employed is a literature review using primary data from Al-Qurthubi’s Tafsir. The findings reveal that early childhood education, according to Al-Qurthubi, particularly in Surah Maryam verse 12, centers around Al-Qur’an education. Memorizing and practicing Al-Qur’an are integral parts of this education. Al-Qur’an education should ideally commence during early childhood, around the ages of 2-3 years. At this stage, it is crucial to introduce children to the oneness of Allah (Tawhid) and teach them the fundamental declaration of faith (Kalimat Tauhid). This research provides fresh insights into early childhood education within Islam. By studying Al-Qur’an from an early age, it is hoped that children will grow into individuals who are faithful and possess noble character.